Spatially anisotropic S = 1 square-lattice antiferromagnet with single-ion anisotropy realized in a Ni(II) pyrazine-n, n'-dioxide coordination polymer - Manson, JL; Pajerowski, DM; Donovan, JM; Twamley, B; Goddard, PA; Johnson, R; Bendix, J; Singleton, J; Lancaster, T; Blundell, SJ; Herbrych, J; Baker, PJ; et al. (American Physical Society, 2023)
The Ni(NCS)2 (pyzdo)2 coordination polymer is found to be an S = 1 spatially anisotropic square lattice with easy-axis single-ion anisotropy. This conclusion is based upon considering in concert the experimental probes x-ray diffraction, magnetic susceptibility, magnetic-field-dependent heat capacity, muon-spin relaxation, neutron diffraction, neutron spectroscopy, and pulsed-field magnetization. Long-range antiferromagnetic (AFM) order develops at TN = 18.5K. Although the samples are polycrystalline, there is an observable spin-flop transition and saturation of the magnetization at ≈80 T. Linear spin-wave theory yields spatially anisotropic exchanges within an AFM square lattice, Jx =0.235 meV, Jy =2.014 meV, and an easy-axis single-ion anisotropy D = −1.622 meV (after renormalization). The anisotropy of the exchanges is supported by density functional theory.